2014
DOI: 10.1002/ente.201402060
|View full text |Cite
|
Sign up to set email alerts
|

Management of Marcellus Shale Produced Water in Pennsylvania: A Review of Current Strategies and Perspectives

Abstract: The reuse of produced water generated by natural gas extraction from Marcellus Shale for hydraulic fracturing is the dominant management option in Pennsylvania (PA), USA. The advantages and disadvantages of this management approach are reviewed and discussed together with long‐term concerns and technology development needs. Abandoned mine drainage is a promising alternative make‐up water, but high sulfate concentrations will lead to barite precipitation once it is mixed with the produced water. Bench‐scale stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Characteristics of these impaired waters sampled from the storage tanks are summarized in Table 5.1. The flowback water used in this study contains much higher concentrations of divalent cations compared with the flowback water from southeast PA reported previously (He et al, 2014a;He et al, 2014c;Kondash et al, 2013) and is in agreement with the water quality model developed by .…”
Section: Characteristics Of Flowback Water and Amdsupporting
confidence: 90%
“…Characteristics of these impaired waters sampled from the storage tanks are summarized in Table 5.1. The flowback water used in this study contains much higher concentrations of divalent cations compared with the flowback water from southeast PA reported previously (He et al, 2014a;He et al, 2014c;Kondash et al, 2013) and is in agreement with the water quality model developed by .…”
Section: Characteristics Of Flowback Water and Amdsupporting
confidence: 90%
“…30,37,60 Proponents argue that it is a plausible option and point to a recent Pennsylvania study, which concluded "a negligible risk to the environment." 61 Due to the accumulation of radioactivity on equipment, future studies should explore radium bioaccumulation in the environment and its impacts on workers. Advanced treatment technologies may prevent discharge of radium species from contaminated equipment and other sources.…”
Section: Discussionmentioning
confidence: 99%
“…59 The disposal of TENORM waste in nonhazardous landfills could result in radiological risks to workers and the public. 30,37,60 Proponents argue that it is a plausible option and point to a recent Pennsylvania study, which concluded “a negligible risk to the environment.” 61…”
Section: Discussionmentioning
confidence: 99%
“…Along with the recovery of treated water from AMD discharge, the membrane concentrate (reject) produced by nanofiltration membranes can also be utilized for the recovery of flowback and produced water generated by the extraction of natural gas from unconventional (shale) reservoirs using hydraulic fracturing. , Recent pilot-scale study showed that mixing AMD with flowback water results in effective removal of barium and strontium while the sulfate concentration in the effluent can be controlled below 100 mg/L by adjusting the mixing ratio of these waste streams. Also, it was shown that >99% of radium in the flowback water can be efficiently removed in the form of Barite sludge by mixing the sulfate containing AMD with flowback water …”
Section: Introductionmentioning
confidence: 99%